Soil Carbon Stabilization Under Coniferous, Deciduous and Grass Vegetation in Post-mining Reclaimed Ecosystems - Nickels, Meghan C. L.; Prescott, Cindy E. (Frontiers in Forests and Global Change, 2021)
Vegetation plays an important role in determining soil organic carbon (SOC) stocks, and influences the mechanisms through which SOC is stabilized within the soil. The type of vegetation selected for use in reclamation may therefore influence the accumulation rate and residence time of SOC in these ecosystems. Earlier studies at reclaimed sites in the Alberta Oil Sands demonstrated that reclaimed ecosystems planted with deciduous trees accumulated the most soil organic matter in the top 10 cm of reclamation material, followed by grass sites, while coniferous sites accumulated the least SOM. The objective of this study was to assess differences in SOC stabilization in the upper 10 cm of soil among revegetated deciduous, coniferous and grass ecosystems 20-40 years following reclamation. We compared soil C in unprotected, physically protected, and chemically protected forms among the three reclamation treatments using density flotation to isolate free particulate (unprotected) SOC from the soil sample, and size fractionation to separate the remaining sample into heavy particulate (physically protected) SOC and mineral-associated (chemically protected) SOC. In addition to this analysis, we used NaOCl oxidation to distinguish chemically resistant and chemically oxidizable C stocks. Chemically resistant C was consistent across all vegetation treatments at approximately 25% of total soil C, while the remaining 75% was chemically oxidizable. Total SOC stocks were also not significantly different among vegetation treatments. Deciduous sites had 57.8 Mg ha-1 SOC, grass sites had 52.7 Mg ha-1 SOC, and coniferous sites had 43.7 Mg ha-1 SOC. Two-thirds of total SOC at grass sites was in protected forms, compared to half of total SOC at coniferous sites and one-third of total SOC at deciduous sites (33.6 Mg ha-1, 22.6 Mg ha-1 and 15.6 Mg ha-1 respectively). Grass sites had significantly more physically protected SOC than deciduous sites while deciduous sites had more unprotected SOC than grass sites. Our findings indicate that the type of vegetation selected for reclaimed areas has important implications for soil carbon in persistent versus unprotected pools.